Internet Gaming Disorder in Adolescents With Psychiatric Disorder: Two Case Reports Using a Developmental Framework - Benarous, Xavier (Front Psychiatry, 2019)
Internet gaming disorder (IGD) has been a controversial entity with various opinions about its clinical relevance as an independent mental disorder. This debate has also included discussions about the relationships between problematic gaming, various psychiatric disorders, and personality traits and dimensions. This paper outlines a developmental-theory based model of Internet gaming misuse inspired by the treatment of two adolescent inpatients. The two clinical vignettes illustrate distinct developmental pathways: an “internalized pathway” via the development of social anxiety, emotional and behavioral avoidance; and an “externalized pathway” with a low level of emotional regulation strategies and impulsivity. In both clinical cases, attachment issues played a key role to understand the specific associations of risk and maintaining factors for IGD, and gaming behaviors may be seen as specific forms of maladaptive self-regulatory strategies for these two youths. These clinical observations support the assumption that gaming use problematic in adolescents should be viewed with a developmental approach, including key aspects of emotional development that represent significant targets for therapeutic interventions.